The language of pluralism from the history of the theory of price determination: Natural price, equilibrium price and administered price - Bloch, Harry (2022)
This paper seeks to identify terminology to aid in distinguishing the approaches to the theory of price determination as presented in classical political economy, neoclassical economics and post-Keynesian economics. Through a review of the respective literature, a dominant usage is identified for the theoretical price concept in each theory. Natural price is identified with classical theory, equilibrium price with neoclassical theory and administered price with post-Keynesian theory. Use of the differentiated terminology is advocated for improving clarity in pluralist discourse on the theory of price determination and the role of prices in modern market economies with their inherent complexity.